The Effect of Discipline, Work Motivation, on Teacher Performance at Senior High School 18 Tangerang Regency - Ideman Junaidi; Maukar Maukar (Dinasti International Journal of Education Management And Social Science, 2022)
The Effect of Discipline and Work Motivation on Teacher Performance at SMAN 18 Tangerang Regency. Thesis 2022. Ideman Junaidi. NPM 91620022. The purpose of this study was to analyze the effect of work discipline and work motivation on teacher performance at SMAN 18 Tangerang Regency. The success of high school graduates cannot be separated from the teacher's performance in the process of teaching and learning activities at school. The main problem in this study was that some teachers did not show optimal performance. Many factors affect performance but in this study analyzes discipline and motivation on teacher performance. The object of research is a teacher at SMA Negeri 18, Tangerang Regency. There are 45 respondents as the sample. Data analysis using descriptive statistics and multiple linear regression analysis techniques to determine the effect partially and simultaneously. From the results of this study partially variable X1 on Y, there is a positive and significant influence between work discipline on teacher performance with a t count of 7.246 > t table of 2.018 and a significance value of 0.000 <0.05. While the variable X2 on Y, there is no positive and significant influence between work motivation on teacher performance with a t count of 0.212 < t table of 2.018 and a significance value of 0.833 > 0.05. Simultaneously there is a positive and significant effect of work discipline, work motivation on teacher performance with a value of 0.000 <0.05. Adjusted R square is 0.804 or 80.4% and the remaining 19.6% is from other variables.